Aplikasi media pembelajaran interaktif berbasis augmented reality pada pengenalan calistung untuk rumah edukasi anak pesisir Desa Percut - Harliana, Putri; Farhana, Nurul Ain; Siregar, Yunita Sari; Ramadhan, Rizki Agung; Ardiantito, Wahyu (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2024)
Nowadays, increasingly rapid technological developments encourage learning progress. However, the method still used remains the same, namely using textbooks and modules. Actually, this method is quite good because the learning system is more technical and structured. In reality, what happens is the opposite, because the increasingly rapid development of technology makes children lazy to read books and more interested in playing games on smartphones. So there is no interest in children learning. Therefore, the author took the initiative to create an interactive and efficient learning media application that can be accessed from a smartphone. It is hoped that this application can increase children's desire to learn starting from an early age, especially at the Coastal Children's Education Center (REDAKSI). The application created is a Reading, Writing and Counting (calistung) learning application aimed at children under the age of ten. This application was created using Unity and contains several learning menus in the application.